Composite materials : properties, characterisation, and applications - Sachdeva, Amit; Singh, Pramod, 1971-; Rhee, Hee Woo (Boca Raton, FL : CRC Press, 2021)
"This book provides an in-depth description of the synthesis, properties, and various characterisation techniques used for the study of composite materials. It also covers applications and simulation tests of these advanced materials. Aimed at industry professionals and researchers, this book offers readers thorough knowledge of the fundamentals as well as advanced level techniques involved in composite material characterization, development, and applications"--
Introduction to composite materials -- Biocomposite and nanocomposite -- Properties of composite materials -- Synthesis of hybrid self-cleaning coating system for construction building glass application -- Experimental and characterization techniques -- Electrical characterization of electro ceramics -- Thermal characterization of composites -- Mechanical characterization techniques of composite materials -- Humidity sensor based on alum-fly ash composite -- Applications of graphene based composite materials as visible range photonic sensors -- Low power Ge-Si0.7Ge0.3 nJLTFET and pJLTFET design and characterization in sub-20nm technology node -- Influence of moisture uptake on mechanical properties of natural fiber reinforced polymer composites -- Exploring the potential of nanotechnology in agriculture: Current research and future prospects -- Nanostructuring of materials by severe deformation processes.
OCLC-licensed vendor bibliographic record.
Keywords: Composite materials; TECHNOLOGY / Material Science; SCIENCE / Mechanics / General; TECHNOLOGY / Engineering / Mechanical